Water management in its mediterranean socio-political context - Busuttil S. (Harmonization and integration of water saving options. Convention and promotion of water saving policies and guidelines, 2007)
Introduction of the seminar : presentation of the water management in its mediterranean socio-political context.
5. WASAMED (WAter SAving in MEDiterranean agriculture) Workshop, 2006/05/03-07, Malta (Malta)